Pengaruh Penyuluhan Kesehatan Tentang Penyakit Stroke Terahdap Tingkat Pengetahuan Keluarga - aditya nur wahyuni; Alfi Faadilah; Alda Nurani Asmara; Akmal Rahayu; Ade Koswara (Yayasan Inspirasi El Burhani, 2021)
Introduction: Stroke is a disease that is a problem in the world, 85% of people in the world have a risk of stroke, this has been recorded by the world stroke organization. This can be avoided if there is awareness to address risk factors early on. Stroke is a disease that affects the whole body, including paralysis, difficulty speaking, emotional difficulties, pain and problems in daily life. Stroke recovery requires a long time and good knowledge about stroke. knowledge. Objective: This counseling aims to determine the extent to which the patient's family understands stroke, risk factors and prevention. One of the main factors of delay in seeking treatment is the lack of knowledge of patients, families and the general public about stroke, signs, symptoms, and a good lifestyle for stroke sufferers. Counseling about stroke if properly explained can encourage stroke patients to seek treatment immediately so that the impact of death and disability can be minimized. Method: The method used in this activity begins with the planning stage, continues with the presentation of the material, and ends with the evaluation to determine the level of success. The presentation of the material was carried out using the lecture method, question and answer with the patient's family and assisted with brochures. Result: The evaluation results show that the activities have been carried out well according to the results indicators and criteria on the evaluation sheet instrument. Coclusion: The sheet is based on five dimensions, namely timeliness and duration, participation, knowledge, job description and problem solving.